Mental Accounting, Financial Literacy, Lifestyle, And Social Environment on Teacher’s Financial Behavior - Zainudin, Amelia Nur Aini; Hariyanto, Dedi; Safitri, Heni (Yayasan Riset dan Pengembangan Intelektual, 2024)
This study aims to investigate the influence of mental accounting, financial literacy, lifestyle, and social environment on the financial behavior of teachers in Sanggau Regency. Data was collected from the Ministry of Education, Culture, Research and Technology in 2023 as well as through questionnaires given to 150 teachers as research samples. The results of the analysis show that the four factors together have a significant effect on teachers' financial behavior. In particular, lifestyle and social environment have a significant influence. The findings provide a deeper understanding of the factors that influence teachers' financial behavior, and provide important insights for the development of programs and policies aimed at improving their financial literacy and financial behavior, thereby creating better financial stability for them.